MAGE-C1 gene and mage-c1 protein expression comparison in primary multiple myeloma patients - E. A. Makunina; L. P. Mendeleeva; V. L. Surin; M. V. Soloviev; M. V. Firsova; A. M. Kovrigina; A. A. Sherstnev; I. V. Gal’tseva; Y. O. Davydova; S. M. Kulikov (Онкогематология)
Background. Nowadays, hematology is a dynamically developing science due to the in-depth study of the molecular mechanisms of a particular disease. A better understanding of oncohematological diseases biology makes it possible to synthesize new targeted drugs, which have a favorable therapeutic effect. In particular, in multiple myeloma, after the introduction of proteasome inhibitors and immunomodulatory drugs into clinical practice, an improvement in overall survival was observed. However, characteristics of the mechanisms of transformation normal plasma cells into malignant ones are still difficult; therefore, the study of the pathobiological basis of multiple myeloma is currently an urgent task.The objective: to evaluate the possible influence of MAGE-C1 gene expression and the presence of mage-c1 protein in patients with newly diagnosed multiple myeloma on the anti-tumor response after bortezomib-containing therapy.Materials and methods. A prospective study included 33 multiple myeloma patients. The diagnosis was established according to International Myeloma Working Group criteria (IMWG, 2014). In 32 patients the induction therapy included bortezomib-containing courses, in one patient lenalidomide was included in the first-line regimens. The MAGE-C1 gene expression by real-time polymerase chain reaction and mage-c1 protein by immunohistochemistry in plasma cells bone marrow, were determined for all patients at the debut of multiple myeloma. As a control group was examined the bone marrow material of healthy donors.Results. When assessment the statistical relationship between the expression of MAGE-C1 gene and mage-c1 protein, it was found that there was no high expression of mage-c1 protein at low values of MAGE-C1 gene expression. At the same time, high expression of the gene was always associated with protein expression above normal values. The analysis aimed at finding the relationship between MAGE-C1 gene and mage-c1 protein detection and the degree of antitumor response after 6 courses of induction therapy showed that high expression of the studied parameters was associated with a worse response to bortezomib-containing treatment.Conclusion. We confirmed that the results of the two methods were comparable. Single factor analysis showed that patients with decreased MAGE-C1 gene and mage-c1 protein expression levels achieved a significantly higher antitumor response to bortezomib-containing regimens, while high expression was accompanied by refractoriness to bortezomib.